Integrating Payment Systems with Social Features: Post-Voucher War Strategies for E-Commerce Sustainability - Rolando, Benediktus (Journal of Business and Economics Research (JBE), 2025)
The Indonesian e-commerce landscape has experienced unprecedented growth, reaching USD 62 billion in gross merchandise value in 2023, yet platforms struggle with sustainability, as evidenced by Bukalapak's exit from the marketplace segment in early 2025 despite substantial technological investments. This research investigates how social commerce features, personalization, and payment convenience influence purchase decisions in e-commerce platforms, with vouchers serving as a mediating variable. The study addresses a critical gap in understanding how platform features, and promotional tools interact to drive purchase decisions in emerging markets, particularly in Indonesia's highly competitive e-commerce sector where platforms engage in intense "voucher wars" for market share. Using path analysis with data collected from 100 active e-commerce users in Indonesia, the research reveals that payment convenience emerges as the strongest predictor of both voucher utilization (t = 7.235, p < 0.001) and purchase decisions (t = 3.356, p < 0.001). Notably, while social commerce features show significant effects through voucher mediation (Sobel Z = 2.4832, p = 0.0130), personalization demonstrates unexpectedly limited impact, challenging assumptions about its universal effectiveness. The study's findings suggest that successful e-commerce platforms in Indonesia must prioritize payment convenience and effectively integrate voucher systems with social commerce features, while potentially reconsidering investments in personalization. These insights contribute to both theoretical understanding of e-commerce dynamics in emerging markets and practical platform development strategies, particularly relevant as Indonesia's e-commerce sector continues its rapid evolution.